Cost-effectiveness of new antiviral treatments for non-genotype 1 hepatitis C virus infection in China: a societal perspective - Li Yang (BMJ Global Health, 2020)
Objective This study aimed to estimate the cost-effectiveness of direct-acting antivirals (DAAs) among patients with non-genotype 1 for the eradication of hepatitis C virus (HCV) infection in China.Methods A decision-analytic Markov model was developed to estimate the lifetime costs, quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs) for DAAs and pegylated interferon plus ribavirin (PEG-RBV) from a societal perspective. The model inputs were derived from the literature, a patient survey, HCV expert opinions and a specialised drug price database available in China. Sensitivity analysis was conducted to evaluate the model robustness and calculate reasonable prices of DAAs.Results For patients infected with HCV genotype 2, the pan-genotypic regimen sofosbuvir/velpatasvir (SOF/VEL) was the most cost-effective strategy compared with PEG-RBV, with an ICER of US$5653/QALY. For genotype 3, the combination of sofosbuvir plus daclatasvir (SOF-DCV) was the most cost-effective approach, with an ICER of US$3314/QALY. All DAA regimens for genotype 6 were cost-saving, and sofosbuvir plus ribavirin (SOF-RBV) was the optimal regimen. One-way sensitivity analysis demonstrated that the ICERs were most sensitive to the utility values, discount rate and drug costs. Probabilistic sensitivity analysis indicated that using a threshold equal to one time the gross domestic product (GDP) per capita in China (US$9769/QALY, 2018), the probability of SOF/VEL, SOF-DCV and SOF-RBV being cost-effective was 58%, 83% and 71% for genotype 2, 3 and 6, respectively. Threshold analysis showed that the price of DAAs should be reduced by some degree to achieve better affordability.Conclusions DAAs were cost-effective compared with traditional treatments. A reasonable reduction in the price of DAAs will increase drug affordability and is of great significance as a global strategy to eradicate viral hepatitis.